Meningioma growth beneath the outer membrane of a traumatic chronic subdural hematoma after burr-hole drainage: a case report and literature review - Xiong, Tao; Liu, Wei-Xian; Tang, Zhu-Xiao; Ma, Jiang-Chun; Sun, Hu (Frontiers in Oncology, 2025)
IntroductionGrowth of meningiomas secondary to postoperative chronic subdural hematoma is extremely rare. Here, we present the first report of a patient who developed a meningioma within the outer membrane of the chronic subdural hematoma after burr-hole drainage for a traumatic chronic subdural hematoma.Case presentationA 75-year-old man underwent burr-hole drainage for a traumatic chronic subdural hematoma on the left side three years prior to presentation. Postoperative follow-up computed tomography revealed no recurrence of chronic subdural hematoma. The patient was admitted because of dizziness and immediately underwent magnetic resonance imaging (MRI), which also showed no recurrence of the chronic subdural hematoma; however, an abnormal signal lesion was identified in the left frontal region. Consequently, an enhanced MRI examination was performed, which indicated significant contrast enhancement, suggesting the diagnosis of meningioma. Subsequently, a frontotemporal craniotomy was performed, and the pathological diagnosis confirmed a meningioma (meningothelial type, World Health Organization grade I). Interestingly, during the craniotomy, the meningioma grew under the outer membrane of the chronic subdural hematoma, fused with the membrane, adhered tightly, and could not be separated. Fifteen months postoperatively, the patient was in good condition with no tumor recurrence.ConclusionsMeningioma growth beneath the outer membrane of traumatic chronic subdural hematoma following burr-hole drainage has not been previously reported, which further highlights the probable significant role of trauma and chronic subdural hematoma-induced inflammatory stimulation in meningioma occurrence and development.